Dispersive waves in functionally graded plates - Ilyashenko Alla; Kuznetsov Sergey (MATEC Web of Conferences, 2018)
The dispersion waves propagating in anisotropic functionally graded (FG) plates with arbitrary transverse heterogeneity and arbitrary elastic monoclinic anisotropy are analysed within a recently developed six-dimensional formalism. The dispersion relation is obtained for all modes of dispersive harmonic waves propagating in an unbounded plate.